ANALISIS WAKAF POLIS ASURANSI PERSPEKTIF HUKUM EKONOMI SYARI’AH DALAM PENGENTASAN PROBLEMATIKA UMAT - Luayyin, Reza Hilmy; M. Nabat Ardli; Moh. Arifin (LPPM STAI Muhammadiyah Probolinggo, 2023)
The concept of waqf also reflects the values of social care and sustainability in Islam.